Oracle® DBA Guide to Data Warehousing and Star Schemas - Scalzo, Bert (Prentice Hall PTR, 2011)
Oracle DBAs finally have a definitive guide to every aspect of designing, constructing, tuning, and maintaining star schema data warehouses with Oracle 8i and 9i. Bert Scalzo, one of the world's leading Oracle data warehousing experts, offers practical, hard-won lessons and breakthrough techniques for maximizing performance, flexibility, and manageability in any production environment.